Tinjauan Hukum Ekonomi Syariah terhadap Pinjaman Online Legal dan Ilegal di Indonesia - Andri Rivai; Diah Mutiara K.; Intan Maulidia Fajri; Haya Zahra (Program Studi Hukum Ekonomi Syariah STAI As-Sunnah Deli Serdang, Sumatera Utara, 2025)
The phenomenon of online lending in Indonesia was examined by focusing on its compatibility and incompatibility with the principles of Islamic economic law. A normative and descriptive approach was applied by analyzing the regulations issued by the Financial Services Authority (OJK), the fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), and empirical data regarding the practices of legal and illegal online lending. It was identified that legal online lending has been regulated under official provisions, allowing legal protection to be provided for consumers, although elements of usury (riba), uncertainty (gharar), and data misuse were still found, which indicated that full compliance with sharia principles has not yet been achieved. Illegal online lending was declared to be in violation of both positive law and sharia principles, as it is operated without license, without supervision, and is characterized by excessive harms such as usurious interest, abusive debt collection, and moral as well as social losses. Based on the perspective of Islamic economic law, legal online lending was considered to have the potential to be directed towards sharia compliance if exploitative and unjust elements are eliminated, whereas illegal online lending was conclusively rejected since its harms were judged to outweigh any benefits.